2000
DOI: 10.1111/j.1553-2712.2000.tb01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism in the Emergency Department: An Epidemiologic Study

Abstract: Abstract. Objective: To describe the epidemiology of alcoholism in ED patients. Methods: Over a twomonth period, every adult patient brought by ambulance to the ED of a large municipal hospital was prospectively enrolled by questionnaire. Data collected included demographics, previous ED use, triage complaint-related diagnoses, hospital admission rates, and ethanol levels (if determined). The CAGE alcoholism questions were administered to all patients by trained assistants. The only exclusion criterion was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 32 publications
2
41
0
1
Order By: Relevance
“…This experiment allowed us to choose flow rates producing ethanol plasma concentrations of approximately 450 mg/dl. This level of ethanol was selected to mimic the exposure received by certain sectors of society who indulge in a repeated high level consumption of ethanol in a short interval ("binge" drinking) leading to severe intoxication (Doyle et al 1994;Parke et al 1996;Whiteman et al 2000).…”
Section: Experimental Designmentioning
confidence: 99%
“…This experiment allowed us to choose flow rates producing ethanol plasma concentrations of approximately 450 mg/dl. This level of ethanol was selected to mimic the exposure received by certain sectors of society who indulge in a repeated high level consumption of ethanol in a short interval ("binge" drinking) leading to severe intoxication (Doyle et al 1994;Parke et al 1996;Whiteman et al 2000).…”
Section: Experimental Designmentioning
confidence: 99%
“…This study was approved by the Institutional Review Board and received exempt status for written consent. Authors from the two prospective studies [6,9] supplied unlinked summary data for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The patients included in Group 2 were typically admitted to "step-down" units, whereas those admitted directly to the ICU were excluded from this group but may have been in Group 1. I Group 3 patients were obtained from a prospective study of ED patients who were identified during a 2-month period as "at risk" for alcohol withdrawal by their affirmative response to 2 or more CAGE questionnaire items [9], thus defining themselves as alcoholics [10,11]. I Group 4 served as a general control for hospital demographics and included all adult ED patients who presented during a 6-month period in 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Although we found documentation of substance problems in approximately 18% of males and 8% of females visiting our ED, our numbers are lower than in some other ED-based studies. Whiteman and colleagues 19 screened 2432 adult patients visiting an inner city US hospital and found evidence of alcohol problems in 24%. In other US studies involving direct patient interviews, researchers found evidence of alcohol problems in 54% of drinking college students presenting to ED, 7 in 43% of young adult drinkers 8 and in 21% of all adult ED patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous studies document a prevalence of substance abuse or dependence in approximately 20% of ED patients. [5][6][7][8][9][10][11][12] Substance abuse has been associated with up to 50% of all injuries. [13][14][15][16][17] Although the bulk of these data is from the United States, the Canadian situation is likely similar.…”
Section: Introductionmentioning
confidence: 99%